Eustasy, high-frequency sea level cycles and habitat heterogeneity - Ramkumar, Mu; Menier, David (Elsevier, 2017)
Eustatic High-Frequency Sea Level Cycles and Habitat Heterogeneity: Basinal-Regional-Global Implications presents the current understanding and future directions of the research on Cretaceous sea level cycles in a single source. This reference work is for beginners, graduates, and postgraduates who are interested in the subject and intend to venture into serious research. This hybrid text/reference is for beginners, academics, and professionals who intend to document sea level dynamics on long and short time scales and resultant habitat and paleobiodiversity changes.